(untitled) (Journal of Engineering, 2016)
The authentic traditional architecture proved that it is very convenient to the environmental and social regulations where it appeared and lasted for hundred of years. This traditional architecture got the intelligence in providing thermal comfort for their occupants by the intelligent usage of the building materials and the intelligent planning and designs which took in consideration the climatic condition and the aerodynamics of the whole city as one ecological system starting from the cold breeze passing through its narrow streets till it enters the dwelling units and glides out through the wind catchers. This architecture had been neglected and replaced by modern imported architecture which had collapsed within few decades not in our region only but all over the world. Now a days the increasing awareness of the global environmental crisis the green or sustainable architecture appeared as a new type of architecture by the eighties of the last century. Today these types of buildings began to enter Arab countries in general and Arabian Gulf countries especially like Masdar city, where smart building can be seen with inelegant treatments which will replace the modern high rise towers with its glass facades. This will lead to the general research problem which concerns the shortage of knowledge about the inelegance in design and planning used in the traditional architecture, and the special research problem concerning the shortage of knowledge concerning the ability to use the inelegant traditional architectural and planning concepts as a base for the future sustainable modern buildings and cites as the aim of this research.